Effect of annual carbon input on soil carbon sequestration and sustainability under rice-wheat cropping system after the 28th crop cycle - DAS, ANUPAM; RAKSHIT, RAJIV; PADBHUSHAN, RAJEEV; KOHLI, ANSHUMAN; ., SUSHANT; KUMAR, SANJAY (Journal of Soil and Water Conservation, 2019)
Retardency of soil organic carbon (SOC) pools play a pivotal role in crop sustainability and future climate change. Thus, a 28-year old long term experiment was used to assess the impact of fertilizer application on plant derived carbon addition, carbon storage and crop sustainability. Addition of organic amendments improved the carbon stock and build up at the rate of 18.1-23.6% and 2.38-2.77 times, respectively over 100 per cent recommended dose of fertilizer (RDF) that augmented carbon sequestration of 6.56-7.91 Mg C ha-1 soil. The annual loss of carbon (C) from existing soil organic matter was 0.769 Mg C ha-1 yr-1 and the decay rate was 0.0587, indicating carbon loss from SOC was 5.9% of the initial SOC content during 28 years of cultivation. Integrated application of organics with inorganic fertilizers enhanced carbon pool index by 27-35 per cent over 100% RDF. Combined application (T5, T6 and T7) improved carbon management index by 21-69% over 100% RDF treatment and retained higher carbon. Addition of organic residues improved the retardency of carbon stock which could have important implications for carbon sequestration.